The Cholinergic Pathways in Inflammation: A Potential Pharmacotherapeutic Target for COPD - Yamada, Mitsuhiro; Ichinose, Masakazu (Frontiers in Pharmacology, 2018)
In COPD, the activity of the cholinergic system is increased, which is one of the reasons for the airflow limitation caused by the contraction of airway smooth muscles. Therefore, blocking the contractive actions with anticholinergics is a useful therapeutic intervention to reduce the airflow limitation. In addition to the effects of bronchoconstriction and mucus secretion, accumulating evidence from animal models of COPD suggest acetylcholine has a role in inflammation. Experiments using muscarinic M3-receptor deficient mice or M3 selective antagonists revealed that M3-receptors on parenchymal cells, but not on hematopoietic cells, are involved in the pro-inflammatory effect of acetylcholine. Recently, combinations of long-acting 2 adrenergic agonists (LABAs) and long-acting muscarinic antagonists (LAMAs) have become available for COPD treatment. These dual long-acting bronchodilators may have synergistic anti-inflammatory effects because stimulation of β2 adrenergic receptors induces inhibitory effects in inflammatory cells via a different signalling pathway from that by antagonizing M3-receptor, though these anti-inflammatory effects have not been clearly demonstrated in COPD patients. In contrast to the pro-inflammatory effects by ACh via muscarinic receptors, it has been demonstrated that the cholinergic anti-inflammatory pathway, which involves the parasympathetic nervous systems, regulates excessive inflammatory responses to protect organs during tissue injury and infection. Stimulation of acetylcholine via the α7 nicotinic acetylcholine receptor (α7nAChR) exerts inhibitory effects on leukocytes including macrophages and type 2 innate lymphoid cells. Although it remains unclear whether the inhibitory effects of acetylcholine via α7nAChR in inflammatory cells can regulate inflammation in COPD, neuroimmune interactions including the cholinergic anti-inflammatory pathway might serve as potential therapeutic targets.